The living church : Convictions of a lifelong pastor - Stott, John R.W. (John Robert Walmsley), 1921- (Nottingham, United Kingdom : Inter-Varsity Press, 2007)
One copy held in FROZEN COLLECTION - Ecclesiology.
PREFACE: "Emerging churches". The postmodern world. 1- Essentials: God's vision for his church. A learning church. A caring church. A worshipping church. An evangelising church. 2- Worship: Glorying in God's holy name. Biblical worship. Congregational worship. Spiritual worship. Moral worship. 3- Evangelism: Mision through the local church. Forms of evangelism. The church must understand itself: its theology. The church must organize itself: Its structures. The church must express itself: Its message. The church must be itself: Its life. 4- Ministry: The twelve and the seven. An every-member ministry. The pastoral ministry. The example of the apostle (the shepherd). The invasion of false teachers (the wolves). The value of the people (the sheep). 5- Fellowship: The implications of koinonia. Our common inheritance. Our common service. Our mutual responsibility. Some practical illustrations. 6- Preaching: Five paradoxes. Biblical and contemporary. Authoritative and tentative. Prophetic and pastoral. Gifted and studied. Thoughtful and passionate. 7- Giving: Ten principles. Springing from the trinity. Creating equality according to our means. Careful supervision and friendly rivalry. A harvest with symbolic significance. The result: Thanksgiving to God. 8- Impact: Salt and light. The truths of salt and light. Weapons for social change. Christian distinctives. CONCLUSION: Looking for Timothys in the twenty-first century. A threefold appeal. Where are the Timothys? Three historical appendices. An autobiographical sketch. (i) Why I am still a member of the Church of England. (ii) I have a dream of a living church. (iii) Reflections of an octogenarian.
a/c 567612. Includes bibliographical references.
Keywords: Church renewal; Church -- Biblical teaching; Church renewal -- Church of England; Pastoral theology